Perspectives internationales sur les mesures d'action positive. Etude comparative dans l'Unione européenne, au Canada, aux Etats-Unis et en Afrique du Sud (Luxembourg, 2009)
"This study was undertaken to help the European Commission develop a framework for better understanding the role that positive action measures can play in practice in preventing or remedying discrimination. In addition, it offered insight into the kind of practical positive action measures already being taken in the EU (and in the EFTA-EEA countries), as well as the possible costs and benefits of the positive action measures. The study also sought to examine how legal frameworks, policies and practices of positive action in the EU compared with Canada, the USA and South Africa."